Answer:
1. 4
2. 5
3. 9
4. 8
5. 100
Step-by-step explanation:
Step-by-step explanation:
We can write
X=-2,-1,0,1,2
And the equation is y=3x+4-------(1)
First we should be put all the value in equation (1)
y=2,1,4,7,10
And the answer will
(x, y) ={ (-2,2),(-1,1),(0,4),(1,7),(2,8)}
Answer:
n= 11/24
Step-by-step explanation:
hope it helps
Step-by-step explanation:
The general equation is y = mx + c...
The given equation is 2x + y = 6
Firstly, move everything on the left except the y to the right.i.e.
y = 6 - 2x
Secondly, rearrange the values on the right to look just like the general equation.
y = -2x + 6
The equation is now in proper general form because it matches the format laid down.